The Role of Locus of Control in Moderating the Effect of Auditor’s Independence and Professional Skepticism on Audit Quality - Intan Nurbaiti Fawziah; Syaiful Iqbal; Sutrisno Trisno (Universitas Hayam Wuruk Perbanas, 2023)
Locus of control (LoC) is an individual's belief in the control of events that can be caused by factors within the individual (internal LoC) and/or factors from outside the individual (external LoC). This study aims to examine the effect of auditor’s independence and professional skepticism on audit quality and find out the role of locus of control (LoC) in moderating the effect of auditor’s independence and professional skepticism on audit quality. An online survey is conducted on 67 respondents (auditors) working at the Big-Four Accounting Firms. This research is a quantitative research with the aim to test the hypotheses. The method used to quantify data is to give weight or attributes in the form of numbers to the data so that it can be processed using modeling and quantitative tools. The results show that auditor’s independence and professional skepticism have a positive effect on audit quality. Internal locus of control strengthens the effect of auditor’s independence and professional skepticism on audit quality. Conversely, the external locus of control weakens the effect of auditor’s independence and professional skepticism on audit quality. The results of this study indicate that auditors often face external pressure during the audit process, which has negative consequences for the quality of audited financial reports.